Effect of electrical parameters on performance of Cu-TiC mixed ceramic compact electrode in EDM process - Khan, Ahsan Ali; Ndaliman, Mohammed Baba; Mohammad , Yeakub Ali; Lawal, Sunday Albert; Sulong, Nurul Farhana; Mohamad, Ummu Atiqah Khairiyah (2013)
Electrical discharge machining (EDM) is one of the most extensively used non conventional material removal processes to machine very hard material. Such materials like hardened tool steel, titanium and its alloy, Hastelloy which were hitherto difficult to machine can be easily processed with EDM. Tool electrode being the main component of the machine can be produced by a number of techniques. This paper evaluates the machining performance of powder metallurgy (PM) electrodes compacted from titanium carbide and copper powders with selected EDM parameters on mild steel material. The Cu-TiC electrodes made up of 70% of titanium carbide and 30% of copper were compacted at a pressure of 6,000 psi (41.34 MPa). Machining was conducted with the peak current, pulse duration and pulse interval as the electrical input variables. The output variables of the investigation were the material removal rate (MRR) and tool wear rate (TWR). The general behaviors of the outputs under the influence of the electrode with the EDM variables have been presented in terms of their 3-D surface plots. Analysis of the results carried out with Design Expert software showed that both the peak current and the pulse duration influences the level of MRR attained. The highest MRR of 9.93mg/min was obtained with the current of 6.5A and pulse duration of 7.5 μs. The TWR are generally high compare to the MRR, with the lowest being 11.30 mg/min. This is one of the attributes that make such electrodes suitable for layer generation on workpiece. All the three input variables show significant influence on the TWR values obtained.